The utility of shift-sampling method to enhance the precision of the calculation of gravity effect in frequency domain · - Thanh, Đỗ Đức (Vietnam Journal of Earth Sciences, 2018)
20 and 30 graviy inversion in frequency domain was widely applied in the interpretation of potential field data, because, unlike the interpretation in space domain, it permits to reduce significaltly computer time. Precision of the interpretation in frequency domain is dependent upon the precision of the transformation between the space and frequency domain. This precision can be improved by the shift - sampling method, which is based on the discrete Fourier transform (OFT) deviation equation. In this paper, shift sampling method is applied to estimate it·s utilization in the calculation gravity effect on both 20 and 30 mathematical models, in which an infinite horizontal cylinder is used as 20 model and a sedimentary basin approximated by vertical rectangular prisms is used as 30 model. With application of shift- sampling method, precision of the calculation gravity effect in frequency domain is enhanced. For both models, root-meansquare error reduced by several tens times. This makes gravity anomaly calculated in frequency domain almost exactly in consistence with the gravity anomaly calculated in space domain. Therefore this method helps in the solving the problem of gravity inversion in consistence frequency domain.